2022
DOI: 10.1007/s12144-022-03456-6
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Tetrad, cybervictimization, and cyberbullying: The role of moral disengagement

Abstract: Cyberbullying is a form of antisocial online behaviors. Perpetration of intentional and repeated harm inflicted through electronic devices is associated with dark personality traits and may be caused by morally impaired reasoning. In the current study, we investigated the associations between the Dark Tetrad (narcissism, Machiavellianism, psychopathy, sadism), cybervictimization, and cyberbullying. We also examined the intervening role of moral disengagement in the relationship between the Dark Tetrad and cybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…Mach has been further linked to higher engagement in cyberbullying (Brown et al, 2019; Gajda et al, 2022; Giumetti et al, 2022; Goodboy & Martin, 2015; van Geel et al, 2017), with decreased empathy (Yuan et al, 2020) and beliefs in human virtue (partially) mediating this association (Zhang & Zhao, 2020). Wang et al (2016) have found that Mach predicted cyberbullying even when moral disengagement (which is a broad concept including dehumanization; Bandura et al, 1996) has been controlled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mach has been further linked to higher engagement in cyberbullying (Brown et al, 2019; Gajda et al, 2022; Giumetti et al, 2022; Goodboy & Martin, 2015; van Geel et al, 2017), with decreased empathy (Yuan et al, 2020) and beliefs in human virtue (partially) mediating this association (Zhang & Zhao, 2020). Wang et al (2016) have found that Mach predicted cyberbullying even when moral disengagement (which is a broad concept including dehumanization; Bandura et al, 1996) has been controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on (cyber)bullying have situated Mach in the Dark Triad (comprising Mach along with self‐promotional narcissism as well as aggressive and impulsive psychopathy ) or Tetrad of personality (Dark Triad extended by sadism , i.e., a pattern of deriving enjoyment from others' suffering). These studies have frequently used multiple regression or structural equation models to pinpoint “unique” contributions of each trait in predicting (cyber)bullying behaviors and have oftentimes found Mach to be (almost) unrelated to (cyber)bullying after partialing (Brown et al, 2019; Gajda et al, 2022; Goodboy & Martin, 2015; Knight et al, 2018; Lau & Marsee, 2013; Pabian et al, 2015; van Geel et al, 2017; for exceptions, see Giumetti et al, 2022; Safaria et al, 2020; Schade et al, 2021; Wright et al, 2020). A critique labeled perils of partialing mentions that controlling for shared variances among the traits of the Dark Triad/Tetrad jeopardizes interpretations because partialing also eliminates desired commonalities among the traits (e.g., antagonism; Rose et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on F2FB and CB have situated Mach in the Dark Triad (comprising Mach along self-promotional narcissism and aggressive and impulsive psychopathy) or Tetrad of personality (Dark Triad extended by sadism, representing deriving enjoyment from others' suffering). These studies often used multiple regression or structural equation models to pinpoint "unique" contributions of each trait in predicting (cyber)bullying behaviors and oftentimes found Mach to be (almost) unrelated to (cyber)bullying after partialing (Brown et al, 2019;Chabrol et al, 2009;Gajda et al, 2022;Gibb & Devereux, 2014;Goodboy & Martin, 2015;Knight et al, 2018;Lau & Marsee, 2013;Nappa et al, 2019;Pabian et al, 2015;van Geel et al, 2017; for exceptions, see Giumetti et al, 2022;Safaria et al, 2020;Schade et al, 2021;Wright et al, 2020). A critique labeled perils of partialing mentions that controlling for shared variances among the traits of the Dark Triad/Tetrad jeopardizes interpretations because partialing also eliminates desired commonalities among the traits (e.g., antagonism; Sleep et al, 2017;Vize et al, 2018).…”
Section: The Dark Triad and Dark Tetradmentioning
confidence: 99%
“…Multidimensional assessments have seldom been applied (i.e., separated verbal, relational, and physical bullying scores) so that broad, undifferentiated operationalizations of bullying can be methodological limitations (Gajda et al, 2022;Volk et al, 2021). As recommended by these authors, and to address the question of whether different sorts of bullying are equivalent from a psychological perspective (Cornell et al, 2006), the first objective pursued in this research was developing a multidimensional (cyber)bullying assessment that separates relational, verbal, and physical aspects.…”
Section: Introductionmentioning
confidence: 99%